Implementação de um modelo computacional para estudo do processo Fischer-Tropsch em reator de leito de lama - Bezerra, Marcio Barbalho Dantas (2010)
This work aims at the implementation and adaptation of a computational model for the study of the Fischer-Tropsch reaction in a slurry bed reactor from synthesis gas (CO+H2) for the selective production of hydrocarbons (CnHm), with emphasis on evaluation of the influence of operating conditions on the distribution of products formed during the reaction.The present model takes into account effects of rigorous phase equilibrium in a reactive flash drum, a detailed kinetic model able of predicting the formation of each chemical species of the reaction system, as well as control loops of the process variables for pressure and level of slurry phase. As a result, a system of Differential Algebraic Equations was solved using the computational code DASSL (Petzold, 1982). The consistent initialization for the problem was based on phase equilibrium formed by the existing components in the reactor. In addition, the index of the system was reduced to 1 by the introduction of control laws that govern the output of the reactor products. The results were compared qualitatively with experimental data collected in the Fischer-Tropsch Synthesis plant installed at Laboratório de Processamento de Gás - CTGÁS-ER-Natal/RN